ANTIOXIDANT CONTENT IN ROMANIAN TRADITIONAL DISTILLED ALCOHOLIC BEVERAGES - MUREȘAN, Bianca; CIMPOIU, Claudia; HOSU, Anamaria; BISCHIN, Cristina; GÁL, Emese; DAMIAN, Grigore; FISCHER-FODOR, Eva; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This is a first detailed analysis of the antioxidant activity in traditional fruit-derived distilled alcoholic beverages from Romania (țuica). A distinctly highest activity, paralleled by Folin-Ciocalteu data and UV-vis absorbances, was seen in the most common type of such brandy, made of plums; other samples included brandies made of apples, pears, fruit mixtures, wine, and cereals. In fact, the values seen for the plum brandy were, even before maturation with wood, similar to those of commercially-available wood-maturated whisky. Increases of up to one order of magnitude in antioxidant activity were seen in all brandies upon maturation with various types of wood – with mulberry tree by far the most efficient, followed by oak and cherry – and with lowest values seen for acacia. Attempts to identify anticancer activity in concentrated extracts prepared from plum brandy, failed. Copper electron paramagnetic (EPR) signals are shown for the first time in such brandy samples.